Waiting to Be Asked: Gender, Power, and Relationship Progression Among Cohabiting Couples - Sassler, Sharon (2010)
The majority of young married Americans lived with their spouses before the wedding, and many cohabited with partners they did not wed. Yet little is known about how cohabitating relationships progress or the role gender norms play in this process. This article explores how cohabiting partners negotiate relationship progression, focusing on several stages where couples enact gender. Data are from in-depth interviews with 30 working-class couples (n = 60). The women in this sample often challenged conventional gender norms by suggesting that couples move in together or raising the issue of marriage. Men played dominant roles in initiating whether couples became romantically involved and progressed to a more formal status. Although women and men contest how gender is performed, cohabiting men remain privileged in the arena of relationship progression. The findings suggest that adherence to conventional gender practices even among those residing in informal unions perpetuates women’s secondary position in intimate relationships.